The Development and Operation of 100% Low Floor Light Rail Vehicles - LI Gang; LI Fu; HUANG Yun-hua (机车电传动)
With analysis and research of 100% low floor LRVs technology, the development and current status of low floor LRVs was described. Taking 100% low floor LRVs at home and abroad as example, technology and application of 100% low floor LRVs was discussed, and the prospect of 100% low floor LRVs in China was elucidated.